On the questions of an expression towards symbolical architecture - Serafin, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The article draws attention to two seemingly different approaches to the creation of an architectural form: the symbolic and the expressive, both in the context of their confrontation, and symbiosis. Symbol clearly supports the generation of the visual communication, while the escalation of the expression prevents a creativity from escaping in the literality and also it enriches the work of an individual element. Both those trends complementary creates the mechanism of modern architecture development, which obviously requires a consideration in the background of the extensive cultural context.